Crítica de libros. Delcambre, Anne-Marie (2006): Las prohibiciones del Islam; Morales, José (2006): Caminos del Islam; Pera, Marcello y Ratzinger, Joseph (2006): Sin raíces: Europa, Relativismo, Cristianismo, Islam - Alonso, Antonio (UNISCI Discussion Papers, 2007)
Sin resumen